2018
DOI: 10.1111/jvh.13034
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of changes in intrahepatic immune cell populations during HCV treatment with sofosbuvir and ribavirin

Abstract: Summary Treatment of chronic hepatitis C virus (HCV) infection with direct‐acting antivirals (DAAs) results in a sustained virologic response (SVR) in most patients. While highly efficacious, ~3%‐5% of patients do not achieve SVR despite having virus that appears susceptible. It is unclear whether host factors contribute to treatment failures, although innate and adaptive immunity may play a role. Previous studies showed that after DAA treatment, the composition of intrahepatic immune cells does not normalize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
2
9
1
3
Order By: Relevance
“…11,12,15 Moreover, the reduction of intrahepatic CD8 + T cell density is the predominant change that has been detected in liver biopsies of DAA treated patients. 16 Nonetheless, we found a reduction of CD8 + T cells only in patients who were treated with RBV-free DAA regimens, and, on the contrary, an increase in others. The reasons for these discrepant results remain unclear, and are probably multifactorial.…”
Section: Discussioncontrasting
confidence: 52%
“…11,12,15 Moreover, the reduction of intrahepatic CD8 + T cell density is the predominant change that has been detected in liver biopsies of DAA treated patients. 16 Nonetheless, we found a reduction of CD8 + T cells only in patients who were treated with RBV-free DAA regimens, and, on the contrary, an increase in others. The reasons for these discrepant results remain unclear, and are probably multifactorial.…”
Section: Discussioncontrasting
confidence: 52%
“…Similarly, in clinical trials, Cody Orr et al speculated that the decrease of population of CD8+ T cells may be due to a decrease in HCV concentration, contributing to an intrahepatic cellular response to reduction in viral burden. In addition, the population of CD4+T cells also declined in the non-parenchymal region of liver, while the significant variation of frequencies of Kupffer cells associated with inflammation was not observed [70].…”
Section: Rehabilitation Of Immune Damagementioning
confidence: 88%
“…Chronic HCV infection is known to quite extensively affect the innate immune response, with an upregulation of interferon‐stimulated genes (ISG) both at intrahepatic and peripheral levels . Notably, a very recent study showed dynamic changes of the innate immune response in HCV patients under DAA treatment, with decreased levels of circulating ISG‐related chemokines at week 2 of therapy followed by a significant increase at weeks 4/8 . Thus, the very potent and rapid effect of the DAA cure may provoke changes in the innate immune response at systemic level and may indirectly influence clinical manifestations and outcomes of different diseases concomitant with CHC.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Notably, a very recent study showed dynamic changes of the innate immune response in HCV patients under DAA treatment, with decreased levels of circulating ISG-related chemokines at week 2 of therapy followed by a significant increase at weeks 4/8. 8,9 Thus, the very potent and rapid effect of the DAA cure may provoke changes in the innate im- during and after DAA treatment with the hope for obtaining important information about the pathogenesis of cutaneous psoriasis and possible new routes of therapeutic approaches for its cure.…”
Section: Re Sultsmentioning
confidence: 99%